2023
DOI: 10.3389/fimmu.2023.1147528
|View full text |Cite
|
Sign up to set email alerts
|

A novel zinc metabolism-related gene signature to predict prognosis and immunotherapy response in lung adenocarcinoma

Abstract: BackgroundZinc is a key mineral element in regulating cell growth, development, and immune system. We constructed the zinc metabolism-related gene signature to predict prognosis and immunotherapy response for lung adenocarcinoma (LUAD).MethodsZinc metabolism-associated gene sets were obtained from Molecular Signature Database. Then, the zinc metabolism-related gene signature (ZMRGS) was constructed and validated. After combining with clinical characteristics, the nomogram for practical application was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…GSE169077 consists of 5 normal samples and 6 OA samples, while GSE55235 contains 10 normal samples and 10 OA samples. ZMRGs were from MSigDB [ 11 ], resulting in 886 ZMRGs after removing duplicate genes (Supplementary Table 1 ). A brief workflow for this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…GSE169077 consists of 5 normal samples and 6 OA samples, while GSE55235 contains 10 normal samples and 10 OA samples. ZMRGs were from MSigDB [ 11 ], resulting in 886 ZMRGs after removing duplicate genes (Supplementary Table 1 ). A brief workflow for this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%